Uji Banding Efektivitas Kalsipotriol Topikal, Suction Blister Grafting dan Kombinasi Keduanya pada Terapi Repigmentasi Lesi Vitiligo Stabil - Diana Nurhayati (MEDIA MEDIKA INDONESIANA, 2012)
Comparison study the efficacy of topical calcipotriol, suction blister grafting and combination of both therapies for repigmentationc of stable vitiligoBackground: Stable vitiligo is defined as non-progressive vitiligo for more than 6-month. A large variety of therapeutic agents are being tried, but an optimal treatment is not yet available. Topical calcipotriol is one of those agent that hypothetically can stimulate repigmentation of vitiliginous lesions. Suction-blister-grafting (SBG), is one of the surgical therapies for replenishment of melanocytes in stable vitiligo. The aim of this study was to compare the efficacy of topical calcipotriol, SBG and the combination of both therapies in the treatment of stable vitiligo.Methods: Twenty-one stable vitiligo (focal, segmental, and generalized) patients were selected for study. Patients were divided into three groups. First-groups were advised to apply topical calcipotriol (50ug/mg) twice-daily over the vitiliginous patches. Secondgroups were given with SBG, and third-groups were given with combination of both treatments. The main outcome measurement was the evaluation of the percentage of repigmentation in treated target lesions in 12-weeks.Results: After12-weeks periods, the combination therapies were found more effective than single therapy. The combination therapies-treated areas showed marked intense repigmentation improvement 19.1% compared to 15.1% on the SBG-only side (p<0.05). Calcipotriol was found to induce initiating repigmentation, but was not statistically significant.Conclusion: Combination therapy of SBG and topical calcipotriol is more effective than single therapy for stable vitiligo.Keywords: Stable vitiligo, suction-blister-grafting, calcipotriol, repigmentation.ABSTRAK Pendahuluan: Vitiligo stabil merupakan vitiligo yang tidak berkembang dalam jangka waktu minimal 6 bulan. Berbagai jenis terapi telah banyak dicoba, akan tetapi terapi yang optimal belum tersedia sampai saat ini. Kalsipotriol topikal merupakan salah satu bahan yang diduga mampu menstimulasi repigmentasi pada lesi vitiligo. Suction blister grafting (SBG) merupakan salah satu tindakan bedah yang dapat dipakai untuk mengganti melanosit pada vitiligo stabil. Tujuan penelitian adalah untuk membandingkan efektivitas kalsipotriol topikal, SBG dan kombinasi keduanya untuk terapi vitiligo stabil.Metode: Penelitian ini dilakukan pada dua puluh satu pasien vitiligo stabil (fokal, segmental dan generalisata). Pasien dibagi menjadi tiga kelompok. Kelompok pertama diberi kalsipotriol topikal (50ug/mg) dioleskan dua kali/hari, kelompok kedua dilakukan tindakan suction blister grafting, dan kelompok ketiga diberi keduanya. Hasil dinilai berdasarkan persentase repigmentasi pada area yang di terapi pada akhir minggu ke-12.Hasil: Pada akhir minggu ke-12, terapi kombinasi terbukti lebih efektif daripada terapi tunggal. Pada lesi yang diterapi kombinasi tampak adanya perbaikan repigmentasi 19,1% dibandingkan terapi SBG tunggal yang 15,1% (p<0,05). Kalsipotriol juga terbukti dapat memicu terjadinya repigmentasi awal, meskipun repigmentasinya secara statistik tidak signifikan.Simpulan: Kombinasi terapi SBG dan kalsipotriol topikal merupakan terapi yang lebih efektif dibandingkan dengan terapi tunggal pada terapi vitiligo stabil